Editing of misaminoacylated tRNA controls the sensitivity of amino acid stress responses in Saccharomyces cerevisiae - Mohler, Kyle (Nucleic Acids Res, 2017)
Amino acid starvation activates the protein kinase Gcn2p, leading to changes in gene expression and translation. Gcn2p is activated by deacylated tRNA, which accumulates when tRNA aminoacylation is limited by lack of substrates or inhibition of synthesis. Pairing of amino acids and deacylated tRNAs is catalyzed by aminoacyl-tRNA synthetases, which use quality control pathways to maintain substrate specificity. Phenylalanyl-tRNA synthetase (PheRS) maintains specificity via an editing pathway that targets non-cognate Tyr-tRNA(Phe). While the primary role of aaRS editing is to prevent misaminoacylation, we demonstrate editing of misaminoacylated tRNA is also required for detection of amino acid starvation by Gcn2p. Ablation of PheRS editing caused accumulation of Tyr-tRNA(Phe) (5%), but not deacylated tRNA(Phe) during amino acid starvation, limiting Gcn2p kinase activity and suppressing Gcn4p-dependent gene expression. While the PheRS-editing ablated strain grew 50% slower and displayed a 27-fold increase in the rate of mistranslation of Phe codons as Tyr compared to wild type, the increase in mistranslation was insufficient to activate an unfolded protein stress response. These findings show that during amino acid starvation a primary role of aaRS quality control is to help the cell mount an effective stress response, independent of the role of editing in maintaining translational accuracy.